BETting on a Transcriptional Deficit as the Main Cause for Cornelia de Lange Syndrome - García-Gutiérrez, Pablo; García-Domínguez, Mario (Frontiers in Molecular Biosciences, 2021)
Cornelia de Lange Syndrome (CdLS) is a human developmental syndrome with complex multisystem phenotypic features. It has been traditionally considered a cohesinopathy together with other phenotypically related diseases because of their association with mutations in subunits of the cohesin complex. Despite some overlap, the clinical manifestations of cohesinopathies vary considerably and, although their precise molecular mechanisms are not well defined yet, the potential pathomechanisms underlying these diverse developmental defects have been theoretically linked to alterations of the cohesin complex function. The cohesin complex plays a critical role in sister chromatid cohesion, but this function is not affected in CdLS. In the last decades, a non-cohesion-related function of this complex on transcriptional regulation has been well established and CdLS pathoetiology has been recently associated to gene expression deregulation. Up to 70% of CdLS cases are linked to mutations in the cohesin-loading factor NIPBL, which has been shown to play a prominent function on chromatin architecture and transcriptional regulation. Therefore, it has been suggested that CdLS can be considered a transcriptomopathy. Actually, CdLS-like phenotypes have been associated to mutations in chromatin-associated proteins, as KMT2A, AFF4, EP300, TAF6, SETD5, SMARCB1, MAU2, ZMYND11, MED13L, PHIP, ARID1B, NAA10, BRD4 or ANKRD11, most of which have no known direct association with cohesin. In the case of BRD4, a critical highly investigated transcriptional coregulator, an interaction with NIPBL has been recently revealed, providing evidence on their cooperation in transcriptional regulation of developmentally important genes. This new finding reinforces the notion of an altered gene expression program during development as the major etiological basis for CdLS. In this review, we intend to integrate the recent available evidence on the molecular mechanisms underlying the clinical manifestations of CdLS, revising the data in favor of a transcription-centered framework, which support the idea that CdLS could be conceptualized as a transcriptomopathy.